A composite electrolyte precursor, a preparation method and application thereof
Patent Information
- Application Number
- CN202510581564.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-07
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-05-07
AI Technical Summary
[0004]有鉴于此,本发明提供了一种复合电解质前驱体及其制备方法和应用,以解决现有无机固态电解质的制备工艺复杂,界面阻抗较大,以及聚合物固态电解质的离子电导率较低的问题
本发明的提供的复合电解质前驱体在电池中原位聚合后生成的复合电解质具有优异的电化学性能,其以具有阻燃性能并可以促进锂盐解离的氧化铝纤维膜为原位聚合的三维骨架,以溶剂化离子液体作为锂离子传导的活性部分,并加入聚合物基质和引发剂经原位聚合得到,制备方法简单高效;并且本发明的复合电解质前驱体以溶剂化离子液体作为锂离子导体,可以保证复合电解质具有高的离子电导率和电化学稳定性;另外,经过原位热聚合工艺,预聚液能够充分润湿电极,固化后能够保持良好的接触,从而可以有效降低界面阻抗。
Smart Images

Figure CN120089798B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and in particular to a composite electrolyte precursor, its preparation method, and its application. Background Technology
[0002] With the rapid development of new energy technologies, the market is increasingly demanding high-energy-density energy storage devices. Lithium-ion batteries have attracted widespread attention in the new energy field due to their high energy density and long cycle life. However, traditional lithium-ion batteries all use liquid electrolytes, which pose safety issues such as leakage or fire. To improve battery safety, using solid-state electrolytes instead of traditional electrolytes is an effective method.
[0003] Solid electrolytes can be mainly divided into inorganic solid electrolytes and polymer solid electrolytes. Compared with polymer solid electrolytes, inorganic solid electrolytes often have higher ionic conductivity at room temperature, generally ranging from 10 to 10. -2 -10 -4 S / cm, such as Li in sulfide systems 10 GeP2S 12 And oxide garnet type Li7La3Zr2O 12 The sulfide solid electrolyte exhibits high ionic conductivity at room temperature comparable to that of liquid electrolytes, reaching up to 10. -2 The S / cm level is high. However, the preparation process of inorganic solid electrolytes is relatively complicated, and the poor contact between them and the electrodes results in a large interfacial impedance, which seriously hinders their application in lithium batteries. Compared with inorganic solid electrolytes, polymer solid electrolytes have better interfacial compatibility and good flexibility. In recent years, polymer solid electrolytes with organic components such as polyethylene oxide (PEO) and polyvinylidene fluoride (PVDF) have received widespread attention and research. This is due to the fact that the polar groups of polymers can complex with alkali metal salts. However, polymers have a certain degree of crystallinity, which restricts the chain segment movement at room temperature. Even if fillers are added to reduce crystallinity and promote ion conduction, the ionic conductivity is still at a low level. Therefore, there is an urgent need to provide an electrolyte with a simple preparation process and high ionic conductivity and low interfacial impedance. Summary of the Invention
[0004] In view of this, the present invention provides a composite electrolyte precursor, its preparation method and application, to solve the problems of complex preparation process and large interfacial impedance of existing inorganic solid electrolytes, and low ionic conductivity of polymer solid electrolytes.
[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: On one hand, the present invention provides a composite electrolyte precursor, comprising a three-dimensional framework and a prepolymer liquid loaded on the three-dimensional framework, wherein the prepolymer liquid is obtained by mixing a solvated ionic liquid, a polymer matrix and an initiator; The three-dimensional framework is an alumina fiber membrane, and the polymer matrix is polyethylene glycol diacrylate or vinylene carbonate.
[0006] Preferably, the mass ratio of the solvated ionic liquid, the polymer matrix, and the initiator is 2:(0.1747-0.8):(0.0124-0.0168).
[0007] Preferably, the thickness of the three-dimensional framework is 100-200 μm, and the loading of the prepolymer onto the three-dimensional framework is ≥0.174 mL / cm². 2 .
[0008] Preferably, the initiator includes one or more of azobisisobutyronitrile and dimethyl peroxide.
[0009] Preferably, the raw materials of the prepolymer liquid further include additives, and the mass ratio of the solvated ionic liquid to the additives is 2:(0.3331-0.4225).
[0010] Preferably, the additive includes one or more of fluoroethylene carbonate and hydrofluoroether.
[0011] On the other hand, the present invention also provides a method for preparing the composite electrolyte precursor according to any one of the above claims, comprising the following steps: (1) The solvated ionic liquid, polymer matrix and initiator are mixed to obtain a prepolymer solution; (2) The three-dimensional framework is immersed in the prepolymer solution to obtain the composite electrolyte precursor.
[0012] Preferably, the mixing is performed by stirring at room temperature for 12-24 hours.
[0013] In another aspect, the present invention also provides the application of the composite electrolyte precursor described in any one of the above claims or the composite electrolyte precursor prepared by the method described in any one of the above claims in a battery.
[0014] Preferably, the application includes assembling the composite electrolyte precursor into a battery and performing an in-situ thermal polymerization reaction to obtain the battery.
[0015] Preferably, the in-situ thermal polymerization reaction is carried out at a temperature of 70-100°C for 1-3 hours.
[0016] This invention provides a composite electrolyte precursor, its preparation method, and its application. Compared with the prior art, its advantages are as follows: The composite electrolyte precursor provided by this invention, after in-situ polymerization in a battery, produces a composite electrolyte with excellent electrochemical performance. It uses an alumina fiber membrane with flame-retardant properties and the ability to promote lithium salt dissociation as the three-dimensional framework for in-situ polymerization, and a solvated ionic liquid as the active component for lithium-ion conduction. The composite electrolyte is obtained by in-situ polymerization with the addition of a polymer matrix and an initiator, making the preparation method simple and efficient. Furthermore, the use of a solvated ionic liquid as the lithium-ion conductor in the composite electrolyte precursor ensures high ionic conductivity and electrochemical stability. Additionally, the in-situ thermal polymerization process allows the prepolymer to fully wet the electrode, maintaining good contact after curing, thereby effectively reducing interfacial impedance. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0018] Figure 1 This is a scanning electron microscope image of the composite electrolyte of Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the composite electrolyte of Comparative Example 1 of the present invention; Figure 3 This is a schematic diagram of the bulk impedance and ionic conductivity of the composite electrolyte at room temperature in Example 1 of the present invention; Figure 4 This is a schematic diagram of the bulk impedance and ionic conductivity of the composite electrolyte in Comparative Example 1 of the present invention at room temperature. Figure 5 This is a graph showing the polarization current of the composite electrolyte in Example 1 of the present invention. Figure 6 The polarization current curve of the composite electrolyte in Comparative Example 1 of this invention is shown. Figure 7 This is the activation energy curve of the composite electrolyte in Example 1 of the present invention; Figure 8 The activation energy curve of the composite electrolyte in Comparative Example 1 of this invention is shown. Figure 9 This is a schematic diagram of the rate performance of a solid-state battery using the composite electrolyte precursor of Example 1 at room temperature according to the present invention. Figure 10 This is a schematic diagram of the rate performance of a solid-state battery using the composite electrolyte precursor of Comparative Example 1 at room temperature according to the present invention. Detailed Implementation
[0019] The present invention will be described below through specific embodiments. Those skilled in the art will understand that the specific embodiments below are merely illustrative and do not limit the scope of the invention in any way. Furthermore, in the following embodiments, unless otherwise specified, the reagents and equipment used are commercially available. If specific processing conditions and methods are not explicitly described in the later embodiments, conditions and methods known in the art can be used for processing.
[0020] In one aspect of the invention, a composite electrolyte precursor is proposed, comprising a three-dimensional framework and a prepolymer liquid loaded on the three-dimensional framework, wherein the prepolymer liquid is obtained by mixing a solvated ionic liquid, a polymer matrix and an initiator, the three-dimensional framework being an alumina fiber membrane, and the polymer matrix being polyethylene glycol diacrylate or vinylene carbonate.
[0021] In some embodiments of the present invention, the molecular weight of polyethylene glycol diacrylate is 600-1000, for example, it can be 600, 700, 800, 900, 1000, etc., and there is no special limitation thereto.
[0022] In some embodiments of the present invention, the initiator is azobisisobutyronitrile.
[0023] In some embodiments of the present invention, the mass ratio of the solvated ionic liquid, the polymer matrix, and the initiator is 2:(0.1747-0.8):(0.0124-0.0168), for example, 2:0.1747:0.0124, 2:0.5:0.015, 2:0.1747:0.0168, 2:0.8:0.0124, 2:0.35:0.0156, etc. Variations in the ratio of the solvated ionic liquid, polymer matrix, and initiator result in variations in the ionic conductivity of the composite electrolyte precursor. Within the range defined in the present invention, this allows the composite electrolyte precursor to possess high ionic conductivity.
[0024] In some embodiments of the present invention, the solvated ionic liquid is prepared from tetraethylene glycol dimethyl ether / triethylene glycol dimethyl ether and lithium bis(trifluoromethanesulfonate)imide, wherein the molar ratio of tetraethylene glycol dimethyl ether / triethylene glycol dimethyl ether and lithium bis(trifluoromethanesulfonate)imide is 1:1. It should be noted that this is only one method for preparing the solvated ionic liquid; other methods disclosed in the prior art can also be used to prepare the solvated ionic liquid.
[0025] Specifically, in a specific embodiment of the present invention, the solvated ionic liquid is prepared by the following method: under a protective atmosphere, tetraethylene glycol dimethyl ether and lithium bis(trifluoromethanesulfonate) imine in a molar ratio of 1:1 are stirred at a temperature of 60-80°C for 24-48 hours until fully mixed to obtain the solvated ionic liquid.
[0026] In some embodiments of the present invention, the thickness of the three-dimensional framework is 100-200 μm, for example, it can be 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, etc., and the loading amount of the prepolymer on the three-dimensional framework is ≥0.174 mL / cm. 2 If the loading of the prepolymer solution is too low, the final battery will malfunction.
[0027] In some embodiments of the present invention, the raw materials of the prepolymer liquid of the composite electrolyte precursor further include additives, wherein the additives are fluoroethylene carbonate. The mass ratio of the solvated ionic liquid to the additive is 2:(0.3331-0.4225), for example, 2:0.3331, 2:0.4, 2:0.4225, etc. Variations in the ratio of the solvated ionic liquid, polymer matrix, initiator, and additive will result in variations in the ionic conductivity of the composite electrolyte precursor. Within the range defined in the present invention, the composite electrolyte precursor can possess high ionic conductivity.
[0028] In another aspect of the present invention, a method for preparing the composite electrolyte precursor described in any one of the above claims is provided, comprising the following steps: (1) The solvated ionic liquid, polymer matrix and initiator are mixed to obtain a prepolymer solution; (2) The three-dimensional framework is immersed in the prepolymer solution to obtain the composite electrolyte precursor.
[0029] In this invention, a solvated ionic liquid, a polymer matrix, and an initiator are first mixed to obtain a prepolymer solution.
[0030] In some embodiments of the present invention, the mixing process of the solvated ionic liquid, polymer matrix and initiator is carried out under a protective atmosphere, such as argon or nitrogen. Specifically, the prepolymer liquid can be prepared in an argon glove box. The mixing is carried out by stirring at room temperature for 12-24 hours, for example, 12 hours, 16 hours, 20 hours, 24 hours, etc.
[0031] In some embodiments of the present invention, when the raw materials of the prepolymer liquid also include additives, the solvated ionic liquid, polymer matrix, initiator, and additives are mixed to obtain the prepolymer liquid. The specific mixing process is the same as when no additives are included, and will not be described again here.
[0032] In this invention, after obtaining the prepolymer solution, the three-dimensional framework is immersed in the prepolymer solution to obtain a composite electrolyte precursor.
[0033] In some embodiments of the present invention, wetting can be achieved by immersing the three-dimensional skeleton in the prepolymer solution or by dripping a sufficient amount of prepolymer solution onto the three-dimensional skeleton. There are no special limitations on how wetting is achieved.
[0034] In some embodiments of the present invention, the three-dimensional framework is an alumina fiber membrane. The alumina fiber membrane is prepared using electrospinning technology, with the following specific steps: aluminum isopropoxide is hydrolyzed using concentrated hydrochloric acid and acetic acid in an ethanol solution; polyvinylpyrrolidone is added as a spinning aid; after uniform stirring, electrospinning is performed to obtain an AlOOH intermediate fiber membrane, which is then calcined at high temperature to obtain the desired alumina fiber membrane. The mass ratio of concentrated hydrochloric acid, acetic acid, ethanol, aluminum isopropoxide, and polyvinylpyrrolidone can be 1:1:8:2:0.3; the spinning voltage is 20-30 kV, for example, 20 kV, 25 kV, 23 kV, etc.; the high-temperature calcination temperature is 600-800℃, for example, 600℃, 700℃, 800℃, and the high-temperature calcination time is 4-6 h, for example, 4 h, 5 h, 6 h, etc. It should be noted that the above is only one method for preparing an alumina fiber membrane; other methods disclosed in the prior art can also be used to prepare alumina fiber membranes.
[0035] In another aspect, the present invention also proposes the application of the composite electrolyte precursor described in any of the above claims or the composite electrolyte precursor prepared by the method described in any of the above claims in a battery.
[0036] In some embodiments of the present invention, the composite electrolyte precursor is assembled into a battery, and then subjected to an in-situ thermal polymerization reaction to obtain the battery. Specifically, the composite electrolyte precursor and electrode materials (e.g., lithium iron phosphate as the positive electrode and lithium sheet as the negative electrode) are assembled together, and then placed in a muffle furnace for an in-situ thermal polymerization reaction to obtain the battery, thereby forming the composite electrolyte through in-situ polymerization on a solid-state battery.
[0037] In some embodiments of the present invention, the temperature of the in-situ thermal polymerization reaction is 70-100°C, for example, 70°C, 80°C, 90°C, 100°C, etc.; the time of the in-situ thermal polymerization reaction is 1-3 hours, for example, 1 hour, 2 hours, 3 hours, etc.
[0038] It is understandable that the longer the in-situ thermal polymerization time and the higher the temperature, the lower the ionic conductivity of the composite electrolyte in the solid-state battery will be, and vice versa. However, the mechanical strength of the composite electrolyte will also decrease. Under the in-situ thermal polymerization reaction conditions specified in this invention, the composite electrolyte can have high ionic conductivity and good mechanical strength.
[0039] The technical solutions of this invention will be clearly and completely described below with reference to specific embodiments. The embodiments of this application are only examples, and all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0040] Example 1
[0041] This embodiment provides a method for preparing a composite electrolyte precursor, the specific steps of which are as follows: (1) In an argon glove box, tetraethylene glycol dimethyl ether and lithium bis(trifluoromethanesulfonate) imine in a molar ratio of 1:1 were stirred at 60°C for 24 h to obtain a solvated ionic liquid. (2) Aluminum isopropoxide was catalytically hydrolyzed in an ethanol solution using concentrated hydrochloric acid and acetic acid. Polyvinylpyrrolidone was added as a spinning aid. After stirring evenly for 12 hours, electrospinning was performed at a spinning voltage of 25 kV to obtain an AlOOH intermediate fiber membrane. The membrane was then calcined at 800°C for 4 hours to obtain an alumina fiber membrane. The mass ratio of concentrated hydrochloric acid, acetic acid, ethanol, aluminum isopropoxide and polyvinylpyrrolidone could be 1:1:8:2:0.3. (3) The solvated ionic liquid, vinylene carbonate, azobisisobutyronitrile and fluoroethylene carbonate were mixed in a mass ratio of 2:0.8:0.0168:0.4225 and stirred at 25°C for 12 h to obtain a prepolymer solution. (4) The prepolymer solution was dropped onto an alumina fiber membrane with a thickness of 100 μm, so that the loading of the prepolymer solution on the alumina fiber membrane was 0.174 mL / cm. 2 A composite electrolyte precursor was obtained.
[0042] Example 2
[0043] This embodiment provides a method for preparing a composite electrolyte precursor, the specific steps of which are as follows: (1) In an argon glove box, tetraethylene glycol dimethyl ether and lithium bis(trifluoromethanesulfonate) imine in a molar ratio of 1:1 were stirred at 60°C for 24 h to obtain a solvated ionic liquid. (2) Aluminum isopropoxide was catalytically hydrolyzed in an ethanol solution using concentrated hydrochloric acid and acetic acid. Polyvinylpyrrolidone was added as a spinning aid. After stirring evenly for 12 hours, electrospinning was performed at a spinning voltage of 25 kV to obtain an AlOOH intermediate fiber membrane. The membrane was then calcined at 600°C for 4 hours to obtain an alumina fiber membrane. The mass ratio of concentrated hydrochloric acid, acetic acid, ethanol, aluminum isopropoxide and polyvinylpyrrolidone could be 1:1:8:2:0.3. (3) The solvated ionic liquid, polyethylene glycol diacrylate, azobisisobutyronitrile and fluoroethylene carbonate were mixed in a mass ratio of 2:0.8:0.0168:0.4225 and stirred at 25°C for 12 h to obtain a prepolymer solution. (4) The prepolymer solution was dropped onto an alumina fiber membrane with a thickness of 100 μm, so that the loading of the prepolymer solution on the alumina fiber membrane was 0.174 mL / cm. 2 A composite electrolyte precursor was obtained.
[0044] Comparative Example 1 This comparative example is basically the same as Example 1, except that the solvated ionic liquid is replaced with a deep eutectic solvent, and the deep eutectic solvent, polyethylene glycol diacrylate, azobisisobutyronitrile and fluoroethylene carbonate are mixed in a mass ratio of 2:0.1747:0.0124:0.3331.
[0045] The deep eutectic solvent is prepared as follows: N-methylacetamide and lithium bis(trifluoromethanesulfonate) in a molar ratio of 3:1 are stirred at 60°C for 12 hours in an argon glove box to obtain the deep eutectic solvent.
[0046] The composite electrolyte precursors of Examples 1-2 and Comparative Example 1 were combined with lithium sheets and lithium iron phosphate, respectively, and assembled into batteries. The battery assembly process was completed in a glove box with oxygen and moisture content below 0.1 ppm. The assembled batteries were then heated in a muffle furnace at 100°C for 60 min for in-situ thermal polymerization to obtain batteries with composite electrolytes.
[0047] like Figure 1 and Figure 2 The images shown are scanning electron microscope (SEM) images of the composite electrolytes of Example 1 and Comparative Example 1 of the present invention, respectively. As can be seen from the images, both the composite electrolytes of Example 1 and Comparative Example 1 are filled with a three-dimensional framework alumina fiber membrane, which is well coupled into a single unit.
[0048] like Figure 3 and Figure 4 The figures show the bulk impedance and ionic conductivity of the composite electrolytes of Example 1 and Comparative Example 1 at room temperature, respectively. It can be seen from the figures that the composite electrolyte of Example 1 has a lower bulk impedance than that of Comparative Example 1; and the ionic conductivity of the composite electrolyte of Comparative Example 1 is 8.93 × 10⁻⁶. -4 The ionic conductivity of the composite electrolyte in Example 1 is 4.32 × 10⁻⁶ S / cm. -3S / cm. This means that compared to composite electrolytes using deep eutectic solvents as lithium-ion conductors, composite electrolytes using solvated ionic liquids as lithium-ion conductors have lower bulk impedance and higher ionic conductivity, which is more conducive to reducing polarization and giving the battery superior electrochemical performance.
[0049] like Figure 5 and Figure 6 The figures show the polarization current curves of the composite electrolytes of Example 1 and Comparative Example 1, respectively. As can be seen from the figures, the lithium-ion transference number of the composite electrolyte of Example 1 is 0.465, while that of the composite electrolyte of Comparative Example 1 is 0.405. That is, compared to the composite electrolyte using a deep eutectic solvent as the lithium-ion conductor, the composite electrolyte using a solvated ionic liquid as the lithium-ion conductor has a higher lithium-ion transference number and can better reduce the influence of concentration polarization.
[0050] like Figure 7 and Figure 8 The figures show the activation energy curves of the composite electrolytes of Example 1 and Comparative Example 1, respectively. As can be seen from the figures, the activation energy of the composite electrolyte of Example 1 is 3.86 kJ / mol, while the activation energy of the composite electrolyte of Comparative Example 1 is 17.92 kJ / mol. That is, compared with the composite electrolyte using a deep eutectic solvent as the lithium-ion conductor, the composite electrolyte using a solvated ionic liquid as the lithium-ion conductor has a lower activation energy level, a lower barrier to lithium-ion transport in its electrolyte, and easier lithium-ion transport.
[0051] like Figure 9 and Figure 10 The figures shown are schematic diagrams illustrating the rate performance of solid-state batteries using the composite electrolyte precursors of Example 1 and Comparative Example 1 at room temperature. Correspondingly, the rate performance data of solid-state batteries using the composite electrolyte precursors of Example 1 and Comparative Example 1 at room temperature are shown in Table 1.
[0052] Table 1
[0053] from Figure 9-10 As can be seen from Table 1, the rate performance of the solid-state batteries of Example 1 and Comparative Example 1 is similar at room temperature. However, compared with the battery using the composite electrolyte precursor of Comparative Example 1, the battery using the composite electrolyte precursor of Example 1 has a higher discharge specific capacity at low rates, indicating that the battery using the electrolyte of the present invention has a stronger energy output capability during discharge.
[0054] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. The application of a composite electrolyte precursor in a battery, characterized in that, The composite electrolyte precursor was assembled into a battery and subjected to an in-situ thermal polymerization reaction to obtain the battery; the in-situ thermal polymerization reaction was carried out at a temperature of 100°C for 1 hour. The composite electrolyte precursor includes a three-dimensional framework and a prepolymer liquid loaded on the three-dimensional framework. The prepolymer liquid is obtained by mixing a solvated ionic liquid, a polymer matrix, and an initiator. The mass ratio of the solvated ionic liquid, the polymer matrix, and the initiator is 2:(0.1747-0.8):(0.0124-0.0168). The raw materials of the prepolymer liquid also include additives, which include one or more of fluoroethylene carbonate and hydrofluoroether, and the mass ratio of the solvated ionic liquid to the additives is 2:(0.3331-0.4225). The three-dimensional framework is an alumina fiber membrane, and the polymer matrix is polyethylene glycol diacrylate or vinylene carbonate. The solvated ionic liquid is prepared by stirring tetraethylene glycol dimethyl ether and lithium bis(trifluoromethanesulfonate) imine in a molar ratio of 1:1 at 60-80°C for 24-48 hours until fully mixed to obtain the solvated ionic liquid. The thickness of the three-dimensional framework is 100-200 μm, and the loading of the prepolymer onto the three-dimensional framework is ≥0.174 mL / cm². 2 .
2. The application of the composite electrolyte precursor according to claim 1 in a battery, characterized in that, The initiator includes one or more of azobisisobutyronitrile and dimethyl peroxide.
3. The application of the composite electrolyte precursor according to claim 1 in a battery, characterized in that, The preparation method of the composite electrolyte precursor includes the following steps: (1) Mix the solvated ionic liquid, polymer matrix, initiator and additives to obtain a prepolymer solution; (2) The three-dimensional framework is immersed in the prepolymer solution to obtain the composite electrolyte precursor.
4. The application of the composite electrolyte precursor according to claim 1 in a battery, characterized in that, The mixing process involves stirring at room temperature for 12-24 hours.
Citation Information
Patent Citations
Preparation and application of organic-inorganic composite solid electrolyte
CN114883637A
Modified high-pressure-resistant gel electrolyte based on lithium nitrate and application of modified high-pressure-resistant gel electrolyte
CN118213613A
Solid electrolyte, secondary battery, preparation method of secondary battery and electric device
CN118589023A
Ion gel, method for producing the same, coating material, negative electrode, and metal secondary battery including the same
JP2024004051A
Non-gas-evolving in-situ cured quasi solid-state batteries
US20240304860A1